Identification of a novel papillomavirus in oral swabs from giant pandas (Ailuropoda melanoleuca) - Zhao, Yi; Zhao, Min; Zhang, Wen (Frontiers in Veterinary Science, 2025)
To fully characterize papillomavirus diversity in giant pandas (Ailuropoda melanoleuca), we identified a novel papillomavirus (named AmPV5, GenBank accession number MZ357114) in oral swabs from giant pandas with the help of viral metagenomics technology in this study. The complete circular genome of AmPV5 is 7,935 bp in length, with a GC content of 39.1%. It encodes five early genes (E1, E2, E4, E6, and E7), two late genes (L1 and L2), and features conserved zinc-binding domains (CXXC- (X)28/29-CXXC) in E6 and E7 genes. E7 protein has an LxCxE domain (pRB binding) in its N-terminal region. The nucleotide sequence of AmPV5 L1 gene shares < 70% identity with other related sequences available in the GenBank database. Phylogenetic analysis indicated that AmPV5 fell within the Lambdapapillomavirus genus but formed a monophyletic branch away from other papillomaviruses found in Ailuropoda melanoleuca, Canis, Felis catus, Panthera uncia, Enhydra lutris, and Procyon lotor. According to the International Committee on Taxonomy of Viruses (ICTV) classification guidelines, AmPV5 is classified as a new species within the Lambdapapillomavirus genus. The discovery provides valuable insights into the viral diversity in giant pandas and highlights the need for continued surveillance of wildlife pathogens. Future studies should explore the potential role of AmPV5 in the health and disease ecology of this endangered species.